Esculpindo na alma do povo a imagem viva de Cristo: a ação do Pe. Francisco Geraedts, S.C.J. - Oliveira, Marlon Anderson de (2009)
In Brazil, the proclamation of the Republic triggered changes between the Church and State, one of the most important being the dissolution of the “Padroado”. The State became secular and the Church, an independent institution. As a consequence, the Church was strongly influenced by the romanization movement, characterized by more control of the Roman Cúria on the Church in Brazil. Simultaneously with the development of romanized catholicism, expressions of faith and popular devotions multiplied in various places in the country, necessitating new directives by the Church. In this context, the work of some congregations like the Fathers of the Sacred Heart of Jesus was remarkable. Our study analyzes the pastoral work of one of their members, Fr. Francisco Geraedts. With carism, creativity and dynamism, he accomplished a formidable work in the Parishes of Colônia Leopoldina (AL) and Água Preta (PE). The incentive to devotions and the arts, united to his missionary spirit were important components in the activites of this Priest who even today, is considered to be a popular saint by the people of those communities.